2018
DOI: 10.1177/1740774518812779
|View full text |Cite
|
Sign up to set email alerts
|

Variance prior specification for a basket trial design using Bayesian hierarchical modeling

Abstract: Background: In the era of targeted therapies, clinical trials in oncology are rapidly evolving, wherein patients from multiple diseases are now enrolled and treated according to their genomic mutation(s). In such trials, known as basket trials, the different disease cohorts form the different baskets for inference. Several approaches have been proposed in the literature to efficiently use information from all baskets while simultaneously screening to find individual baskets where the drug works. Most proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 19 publications
4
48
0
Order By: Relevance
“…While basket trial definitions (n = 35) [[1], [2], [3], [4], [5],11,13,15,18,[23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48]] were consistent on some aspects, such as that basket trials study multiple disease types (n = 34), other features such as the number of interventions to be studied were inconsistent. Approximately half of the reviewed publications (n = 18) [1,2,4,5,11,13,15,25,30,31,33,35,38,39,41,42,45,49] specified that basket trials are designed to evaluate a single intervention, while around a third (n = 10) [3,18,23,[26], [27], [28], [29],36,40,43] stated that they can evaluate multiple interventions. The remaining definitions (n = 7) specified both [37,44,47] or neither [32,34,46,48].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While basket trial definitions (n = 35) [[1], [2], [3], [4], [5],11,13,15,18,[23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48]] were consistent on some aspects, such as that basket trials study multiple disease types (n = 34), other features such as the number of interventions to be studied were inconsistent. Approximately half of the reviewed publications (n = 18) [1,2,4,5,11,13,15,25,30,31,33,35,38,39,41,42,45,49] specified that basket trials are designed to evaluate a single intervention, while around a third (n = 10) [3,18,23,[26], [27], [28], [29],36,40,43] stated that they can evaluate multiple interventions. The remaining definitions (n = 7) specified both [37,44,47] or neither [32,34,46,48].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining definitions (n = 7) specified both [37,44,47] or neither [32,34,46,48]. The number of biomarkers or subgroups studied in a basket trial also varied, with the majority of definitions describing these studies as including only a single biomarker (n = 25) [1,[3], [4], [5],11,13,15,23,[26], [27], [28], [29],[31], [32], [33], [34], [35],[37], [38], [39], [40], [41], [42], [43],45] and considerably fewer including multiple (n = 5) [2,18,25,30,49]. Three basket trials specified the need for seamless design [3,4,39] and one for common control [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A basket trial design using Bayesian hierarchical modeling to borrow information on the treatment effect across different patient subpopulations was proposed by Liu et al 217 In a simulation study, Cunanan et al 218 found that the Bayesian hierarchical model as proposed by Berry et al 219 can have heavily inflated error rates. Cunanan et al 220 further investigated the effect of different priors for the variance parameter in Bayesian hierarchical models, which is directly linked to how much information is shared across subpopulations, on the type 1 error rate. To better control the type 1 error in Bayesian hierarchical models attributable to inappropriately determining the degree of information borrowing, Chu and Yuan 221 proposed a calibrated Bayesian hierarchical model for basket trials in which the shrinkage parameter is defined as a (through simulation calibrated) function of a treatment effect similarity measure.…”
Section: Basket Designs and Methodsmentioning
confidence: 99%
“…Recently, modifications and improvements of the BHM approach have been proposed. Cunanan et al 19 adequately investigated prior specifications on the variance parameter that controls the degree of borrowing information on the response rate across subpopulations. However, BHM assumes that the treatment effect for each subpopulation is exchangeable and localizes around a common mean of distribution on the treatment effect.…”
Section: Introductionmentioning
confidence: 99%